Partnership for mental health development in Sub-Saharan Africa (PaM-D): a collaborative initiative for research and capacity building (2019)
Aims In low and middleincome countries (LMIC) in general and sub-Saharan African (SSA) countries in particular, there is both a large treatment gap for mental disorders and a relative paucity of empirical evidence about how to fill this gap. This is more so for severe mental disorders, such as psychosis, which impose an additional vulnerability for human rights abuse on its sufferers. A major factor for the lack of evidence is the few numbers of active mental health (MH) researchers on the continent and the distance between the little evidence generated and the policymaking process. Methods: The Partnership for Mental Health Development in Africa (PaMD) aimed to bring together diverse MH stakeholders in SSA, working collaboratively with colleagues from the global north, to create an infrastructure to develop MH research capacity in SSA, advance global MH science by conducting innovative public health relevant MH research in the region and work to link research to policy development. Participating SSA countries were Ghana, Kenya, Liberia, Nigeria and South Africa. The research component of PaMD focused on the development and assessment of a collaborative shared care (CSC) program between traditional and faith healers (T&FHs) and biomedical providers for the treatment of psychotic disorders, as a way of improving the outcome of persons suffering from these conditions. The capacity building component aimed to develop research capacity and appreciation of the value of research in a broad range of stakeholders through bespoke workshops and fellowships targeting specific skillsets as well as mentoring for early career researchers. Results: In the research component of PaMD, a series of formative studies were implemented to inform the development of an intervention package consisting of the essential features of a CSC for psychosis implemented by primary care providers and T&FHs. A cluster rand was next designed to test the effectiveness of this package on the outcome of psychosis. In the capacity building component, 35 early and midcareer researchers participated in the training workshops and several established mentor mentee relationships with senior PaMD members. At the end of the funding period, 60 papers have been published and 21 successful grant applications made. CONCLUSION: The success of PaMD in energising young researchers and implementing a cutting-edge research program attests to the importance of partnership among researchers in the global south working with those from the north in developing MH research and service in LMIC.